COLLABORATIVE GOVERNANCE REGIME AND THE RESPONSIVE GOVERNANCE IN OGUN STATE: A STUDY OF OGUN STATE COUNCIL OF ELDERS (Singaporean Journal of Business Economics and Management, 2015)
The public administration system in Nigeria which has been traditional and patterned towards the bazaar canteen model of Riggs has over the years led to gross inefficiency and inability to meet the needs of the citizenry. The failings of the traditional administrative system necessitated an investigation of the adoption of collaborative governance regime as a tool for achieving responsive governance. The study conducted in Ogun State, one of the 36 states in Nigeria, utilized qualitative data, and primary data were collected through interview of 97 respondents drawn from eight selected local governments in the state. The key informants included top government officials at state and local government levels, career civil servants, community leaders, traditional rulers, as well as members of the Ogun State Council of Elders. Data collected were content analyzed. The adoption of collaborative governance between the state government and the Ogun State Council of Elders led to resolution of several crises in the state; economic development programmes and projects; enhancement of qualitative education in the state; effective poverty reduction; and grassroots development. The study suggested that embracing collaborative governance regime in a prismatic society such as Nigeria ensures the attainment of responsive governance in the society, and equally short circuit the excesses of corrupt officials following the involvement of educated and enlightened citizens.